(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Child abuse by another person, whether adult or kid, harms or neglects a child from it. In all cultural, ethnic and socioeconomic groupings, child abuse occurs. Misuse of children may be physical, verbal, emotional, sexual or neglective. Abuse may cause a kid significant damage and even death. A issue that in India has barely begun to emerge The global challenges of gender violence include rape, sexual abuse and sexual harassment.